Educational policies and research itineraries: the São Paulo faz escola Program - Celso do Prado Ferraz Carvalho; Miguel Henrique Russo (Red Latinoamericana de Estudios Epistemológicos en Política Educativa, 2016)
The objective of this study was to understand the foundations and the process of elaboration of contemporary educational policies, as well as the tensions present in education workers‟ resistance to/appropriation of these policies implementation. In this text, we present initial results of the research that studies the "São Paulo faz escola Program" - name given to the São Paulo state education reform implemented from 2007 onward. Initially, educational policies are placed in the broader context of the relation between education and contemporaneity, and the analytical perspective that underlies our analysis is outlined. Following that, we present the context and objectives underlying the "São Paulo faz escola‟ program, as well as the initial results of the research.